The Restive Margins: Comparing the Causes and Resolution of Indonesia’s Regional Rebellions of Aceh and East Timor - Lanti, Irman Gurmilang; Anshori, Muhammad Fikry; Sudirman, Arfin (GoAcademica Research & Publishing, 2024)
This article compares and contrasts the handling of separatist movements and regional rebellions in Indonesia. As a plural society, the Indonesian state has encountered challenges from its margins almost since its birth. However, the challenges do not necessarily always come in the form of secessionism. Some regionally based rebellions also sought to change the state foundation or the way to run the state. This article examines two cases of regional rebellions throughout the nation’s history, i.e., Aceh and East Timor. It contends that Indonesia’s margins revolted from the combination of deprivation factors, such as ideological, economic, political, and identity, which got sidelined as Indonesia spurred on the nation-building effort. The handling of the rebellions has also been varied, with military suppression as the default approach before Reformasi. Reformasi has widened the range of choices of the state in dealing with the separatist challenges.